Implementing Activity-Based Presentation in Higher Education and Describing Presenters' Presentation Skills - Tarwiyah, Siti; Dewi, Nuna Mustikawati; Sari, Betty Fitria Nita; Dani, Muhammad Hirza Qusuma (Vision: Journal for Language and Foreign Language Learning, 2024)
Activity-Based Presentation (ABP) is known for engaging students through experiential tasks. However, its implementation in higher education requires further exploration. This study aims to explain the implementation of ABP and to describe the presenters’ presentation skills. Twenty-six pre-service teachers who attended the English Across Curriculum class became the subjects of this study.  Based on participants’ presentations, the researchers explained the implementation of ABP and described their presentation skills. Data on ABP implementation were analyzed using three stages of the interactive model of analysis: data condensation, data display, and conclusion drawing. Meanwhile, data on the pre-service teachers’ presentation skills were analyzed to determine the mean for each skill. This study shows that participants manage classroom presentations using methods such as ICARE, KWL Chart, Jigsaw, Text-Based Learning, Gallery Walk, Problem-Based Learning, expository, and demonstration. They have relatively good presentation skills, which support the achievement of presentation objectives. The achievement is proven by the audience's good weekly scores. This research exemplifies the enactment of integrated learning, primarily intended to equip pre-service teachers with content knowledge and presentation skills simultaneously. However, further development is needed to make this approach reach a more meaningful and impactful presentation. More studies on ABP also still need to be carried out to enhance its effectiveness.